CONSTRUCTING SKILL TESTS FOR VOLLEYBALL PLAYERS OF KIRKUK EDUCATION TEAM - Ahmed Ali Abdullah Ahmed Al-Jubouri (Proximus Journal Publishing, 2024)
Fourteen purposefully chosen students from the Kirkuk Education Team for the academic year 2022–2023 participated in the research. The General Directorate of Kirkuk Education's indoor sports facilities served as the study site. The objective was to ascertain which skill tests were developed to enhance skill performance in accordance with match rounds and to create skill tests that influence the degree of skill performance during matches. Seven factors—five of which were approved considering the requirements for accepting the factor to represent the skill tests for volleyball players—were determined by the relevance of the correlations between the eleven skill tests
Keywords: Skill Tests; Volleyball; Education Team